Steelmakers: The Marriage of Entrepreneurship and Finance in New Glasgow and Halifax, 1883–1904 - Frost, James (Journal of the Royal Nova Scotia Historical Society, 2022)
One of the most technically advanced, fully integrated steel companies in Canada, the Nova Scotia Steel Company, began as Hope Iron Works, established in 1872 by Graham Fraser and Forrest McKay, two New Glasgow metal workers, with a small investment. In 1882, in response to the 1879 National Policy, Hope was incorporated into a new company with a board consisting mostly of New Glasgow merchants and entrepreneurs and John F. Stairs of Halifax. The Stairs' role in the development of “Scotia,” as it was called, has either been downplayed or largely ignored.From careful beginnings, the new company made rapid progress, installing new machinery and adding many new products. By the summer of 1901 the Nova Scotia Steel and Coal Co. was brimming with optimism and set about the task of becoming a fully integrated steel company. What had begun as a $4,000 investment in 1872 by two New Glasgow visionaries with their eight employees had become, by Nova Scotia standards, an industrial colossus with $4.5 million in assets and well over 1,500 employees at three locations, a triumph of inter-regional cooperation. The process of growth of this industrial giant from such humble beginnings is a tale of Maritime high finance in the era of the National Policy.